BLEOMYCIN INDUCED PULMONARY TOXICITY IN PATIENTS WITH GERM CELL TUMOURS - Usman, Muhammad; Faruqui, Zia Salman; Din, Najam ud; Zahid, Khawaja Farhan (Journal of Ayub Medical College Abbottabad, 2010)
Background: Bleomycin is a cytotoxic drug used in treatment of Germ Cell Tumours (GCTs) and is associated with pulmonary toxicity. Bleomycin pulmonary toxicity (BPT) manifests predominantly as pulmonary fibrosis, organising pneumonia (OP) or Nonspecific Interstitial Pneumonitis (NSIP). Our objectives were to determine the incidence of BPT, describe the common HRCT patterns of pulmonary toxicity and to find out the correlation of variables (cumulative dose of bleomycin, age and glomerular filtration rate) with pulmonary toxicity. Methods: The study included the data of 96 patients from March 2006 to September 2008. All patients had histologically proven GCT and received bleomycin containing regimes. Variables age, GFR at the time of initial presentation along with cumulative dose of bleomycin at completion of chemotherapy or at the time of BPT were recorded. The High resolution CT chest (HRCT) of these patients was independently reviewed by two radiologists. Bleomycin toxicity was reported on the radiologic features of pulmonary fibrosis, OP or NSIP. Results: Fourteen patients (14.6%) developed BPT. Common patterns of BPT were, pulmonary fibrosis (5.2%), OP (5.2%) and NSIP (4.2%). Using the Univariate regression analysis there was significant relationship between BPT and age, cumulative bleomycin dose and initial GFR at the beginning of treatment. Conclusions: Because BPT can be progressive and fatal, early recognition is important. The diagnosis of pulmonary toxicity should be considered in any patient with new or progressive respiratory complaints. BPT can be difficult to diagnose; therefore, knowledge and understanding of radiologic manifestations of toxicity caused by Bleomycin are necessary for institution of appropriate treatment. There is increasing incidence of BPT with increasing age, cumulative dose and decreasing GFR. Keywords: Bleomycin, Pulmonary toxicity, Germ cell tumours, HRCT